A dual approach with lignin and nanolignin: reinforcing UV stability and sustainability in PVA matrices - Freitas, Amanda de Sousa Martinez de; Rodrigues, Jéssica de Souza; Fré, Lucas Victor Benjamim Vasconcelos; Vieira, Henrique Otávio Salles; Nascimento, Maria Eduarda da Silva; Amaro, Stefanny; Emidio, Livia Souza; Araujo, Daniele Ribeiro de; Sepulveda, Anderson Ferreira; Komatsu, Daniel; Botaro, Vagner Roberto; Fraceto, Leonardo Fernandes; et al. (Universidade Federal de São Carlos, 2025)
Kraft lignin (KL) and its acetic acid-fractionated derivatives were evaluated for their antioxidant and ultraviolet C (UV-C)-absorbing properties to mitigate the photooxidative degradation of polyvinyl alcohol (PVA). PVA films were prepared with 4 % (w/w) KL macroparticles - including unfractionated KL and the fractionated forms KL30, KL40, and KL50 - and with 0.4 % (w/w) lignin nanoparticles (NP), derived from the same fractions (named NPKL, NP30, NP40, and NP50). All formulations, including the control (pure PVA), were blended with 10 % (w/w) NPK fertilizer (nitrogen‑phosphorus‑potassium, 10–10-10) and plasticized with glycerol for film casting. After 21 days of UV-C exposure, films containing LNP retained over 90 % transparency, compared to ~70 % for pure PVA. Fourier-transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) confirmed reduced photooxidative and thermal degradation in lignin-containing films, especially those with KL30 and NP30. Biodegradation assays using respirometric CO₂ analysis showed accelerated release for NP30 (up to 90 mg after 20 days), reflecting enhanced microbial activity. Leaching assays demonstrated controlled release of NPK ions over 40 days in films with NP. In mulch film application tests with cherry tomato, PVA + NP30 showed seedling development comparable to commercial mulch and superior to control films. These results confirm the potential of NP as sustainable, multifunctional additives for UV stabilization and controlled nutrient delivery in biodegradable agricultural films.
Uma abordagem dupla com lignina e nanolignina: reforçando a estabilidade aos raios UV e a sustentabilidade em matrizes de PVA
Keywords: Lignin; Nanolignin; PVA; Lignina; Nanolignina; CIENCIAS EXATAS E DA TERRA::QUIMICA